Low-Grade Appendiceal Mucinous Neoplasm Involving the Endometrium and Presenting with Mucinous Vaginal Discharge - Vera Vavinskaya; Joel M. Baumgartner; Albert Ko; Cheryl C. Saenz; Mark A. Valasek (Hindawi Limited, 2016)
Primary appendiceal mucinous lesions are uncommon and represent a spectrum from nonneoplastic mucous retention cysts to invasive adenocarcinoma. Low-grade appendiceal mucinous neoplasms (LAMNs) represent an intermediate category on this spectrum and can be classified according to whether or not they are confined to the appendix. Although LAMNs are frequently confined to the appendix, they can also spread to the peritoneum and clinically progress as pseudomyxoma peritonei (i.e., mucinous ascites). Thus, the appropriate classification of appendiceal primary neoplasia is essential for prognosis and influences clinical management. In addition, the precise classification, management, and clinical outcome of patients with disseminated peritoneal disease remain controversial. Here, we report an unusual case of LAMN with pseudomyxoma peritonei that initially presented with mucinous and bloody vaginal discharge. Pathological evaluation revealed low-grade appendiceal mucinous neoplasm with secondary involvement of the peritoneum, ovaries, and endometrial surface. Therefore, LAMN should be considered in the differential diagnosis of mucinous vaginal discharge.